2005
DOI: 10.1152/ajpendo.00448.2004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 acts as insulin sensitizer on glycogen synthesis in human skeletal muscle cells by phosphorylation of Ser473 of Akt

Abstract: Previous studies showed an insulin-"desensitizing" action of IL-6 on glycogen synthesis in hepatocytes. We recently found no inhibition of the proximal steps of the insulin signal cascade in human skeletal muscle cells. Because these data indicate a possible tissue-specific effect of IL-6, we investigated the influence of IL-6 on insulin-stimulated glycogen synthesis in these cells. At first, we found that incubation of the cells with 20 ng/ml IL-6 alone induced phosphorylation of Ser473 of Akt, but not of Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 36 publications
5
59
1
2
Order By: Relevance
“…For the duration of the clamp, subjects were also infused with either rhIL-6 or sham (control) in a random, repeated-measures, single-blinded fashion. Our pilot work and data from previous studies (9,10,19) demonstrated that IL-6 delivered in 2% human albumin at a rate of 5 g/h would predict a plasma concentration of 100 -140 pg/ml, a level seen with strenuous exercise.…”
Section: Methodsmentioning
confidence: 62%
“…For the duration of the clamp, subjects were also infused with either rhIL-6 or sham (control) in a random, repeated-measures, single-blinded fashion. Our pilot work and data from previous studies (9,10,19) demonstrated that IL-6 delivered in 2% human albumin at a rate of 5 g/h would predict a plasma concentration of 100 -140 pg/ml, a level seen with strenuous exercise.…”
Section: Methodsmentioning
confidence: 62%
“…AMPK phosphorylation Previous studies have reported that IL-6 increases the phosphorylation of AMPK in several different cells [16][17][18][19]. Indeed, phosphorylated AMPK was markedly increased in the IL-6 mice, while gp130 was not altered (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…In contrast to the effects in liver and adipose cells, positive effects have been reported in skeletal muscle in terms of increasing glucose uptake in short-term experiments [17][18][19]. However, the overall importance of these short-term experimental studies is unclear considering that IL-6 levels are chronically elevated in obesity, mainly due to increased production by the adipose tissue and the enlarged fat cells [5,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that infusion of IL6 into patients with type 2 diabetes normalised insulin levels without affecting glucose clearance [11], raising the possibility that acute IL6 infusion may augment insulin sensitivity. In support of this notion, Weigert et al [12,13] recently demonstrated that insulin signalling and glycogen synthesis were increased by IL6 administration in L6 myotubes, while whole-body IL6 knockout renders mice obese and glucose intolerant [14]. In contrast, IL6 treatment impairs liver insulin signalling [15] and leads to impaired insulin action during an insulin tolerance test [16] and a euglycaemic-hyperinsulinaemic clamp [17] in mice.…”
Section: Introductionmentioning
confidence: 96%